Love Expressions in Children's Poems before and after 2000 - Syahruni Junaid; Aan Mujizat; Sumarni Sumarni (UIN Syarif Hidayatullah Jakarta, 2023)
This study explores the expressions of love in children's poems before and after the year 2000. Seeing the differences in the characteristics of the generation of children before and after 2000, this study aims to find out the children's love expressions to their parents through imagery used in poems as a reflection of Birrul Walidain. This research applies the technique analysis from Miles and Huberman, started with data reduction and presentation to finally come to one conclusion. Furthermore, the result of this research found that there is a distinction between love expressions in two different eras. During the era before 2000, the children expressed their gratitude primarily to their parents for their direct emotional bonding. Furthermore, during the era after 2000, the children tended to deliver their hope and pray for their parents, which portrays that the children missed the direct physical connection with their parents because there are almost no narratives that indicated the use of a physical indicator of imagery; however, they still expressed their loves by writing their wishes in their poems.